Textural and functional properties of surimi from striped catfish Pangasianodon hypophthalmus (Sauvage, 1878) as affected by natural spice extracts - Majumdar, Ranendra K.; Saha, Apurba; Maurya, Pradip K.; Roy, Deepayan; Shitole, Snehal; Balange, Amjad K. (Indian Journal of Fisheries, 2016)
Effects of aqueous extract of natural spices such as garlic, clove and cinnamon on the textural and functional properties of surimi gel from Striped catfish, Pangasianodon hypophthalmus (Sauvage, 1878) was studied and a positive effect was observed. Different levels of extract (0.5, 1.0, 1.5 and 2.0%, w/w) were used. Protein solubility significantly (p<0.05) changed in treated gels and major change was found in clove and cinnamon incorporated gels. Water holding capacity of the treated gels were found to be higher compared to control and higher values were observed in respect of treatments with cinnamon and clove than that of garlic. Gel strength of treated samples increased significantly (p<0.05) from the control and maximum was found with clove extract at 0.5% level. Whiteness of gel slightly reduced in treated samples. All the texture profiles differed from the control with maximum hardness in clove extract incorporated gels followed by garlic and cinnamon treated ones.